ANTIHYPERGLYCEMIC, ANTIOXIDANT AND ANTI-INFLAMMATORY EFFECTS OF AQUEOUS EXTRACT OF MISTLETOE (Cladocolea loniceroides) IN STZ-INDUCED DIABETIC MICE - Paredes Ruiz, Frida Monserrat Hosanna; Barrera, Angeles Fortis; Alquicira, Edith Ponce; Almanza Pérez, Julio César; Ramos, Rubén Román; Santos, Jorge Soriano (African Journal of Traditional, Complementary and Alternative Medicines, 2019)
Background: Inhibition of carbohydrate hydrolyzing enzymes, such as α-amylase and α-glucosidase, is a key element in the regulation of diabetes mellitus (DM). The purpose of this work was to study the inhibition of carbohydrate hydrolyzing enzymes, and the antihyperglycemic activity of aqueous extract of Cladocolea (C. loniceroides) in streptozotocin (STZ)- induced diabetic mice. Materials and Methods: The inhibitory activities of C. loniceroides aqueous extract on α-amylase and α-glucosidase were investigated in vitro. Glucose tolerance test was performed in normoglycemic (NG) mice which were fed with starch or sucrose. The effect of mistletoe aqueous extract (ME) was measured in (STZ)-induced diabetic mice. On day 35 of the treatment, the effect of decreasing oxidative stress (lipid peroxidation, glutathione redox state, GPx and GR specific activities, cytokines and aminotransferases analysis) was assessed. Results: ME showed a competitive mode of inhibition for the carbohydrate hydrolyzing enzymes (CHE). The maximum antihyperglycemic activity in mice was observed for the unripe fruit aqueous extract (UFAE) for -amylase and stem aqueous extract (SAE); for -glucosidase due to the glycemic response reduction by 23% or 35%, respectively. UFAE decreased malondialdehyde (MDA) 1.76 times; GSH/GSSG ratio was mantained (3.08 ± 0.66); GPx activity was reduced (24%); IL-6 was reduced (18%) and the concentration of TNF- (37%) was leveled with respect to the (STZ)-induced diabetic mice; ALT and AST (liver transaminases) levels were nearly the same compared with those found in the NG mice. Conclusion: UFAE of C. loniceroides exhibited the highest antidiabetic activity in (STZ)-induced diabetic mice.